(untitled) (Annals of Medical Research, 2023)
Aim: This study seeks to evaluate the awareness and knowledge levels of mothers with children younger than three years old about breast milk and vitamin D. Materials and Methods: A questionnaire containing 14 questions was administered to 405 women who applied to a district state hospital in Turkey. Analyses were conducted using the SPSS (Statistical Package for Social Sciences; SPSS Inc., Chicago, IL) 22.0 application. Results: The knowledge level of the mothers whose education level is high school and above was significantly higher than that of the mothers whose education level is secondary school and below (p=0.005). There was a significant difference between the economic status of mothers in terms of knowledge score (p<0.001). The knowledge score of the mothers who used vitamin D in their last pregnancy was higher than those who did not (p=0.028). The knowledge score of the mothers who gave vitamin D to their last baby was significantly higher than those who did not (p=0.019). There was a significant difference regarding the knowledge score according to the last baby’s first six months of nutritional status (p<0.001) and the number of taking the baby out for vitamin D (p<0.001). Conclusion: It is necessary to inform mothers, fathers, and family elders about breast milk and vitamin D starting from pregnancy. Family physicians, health workers, obstetricians, and pediatricians should constantly emphasize the importance of breast milk and vitamin D supplementation. Breast milk and vitamin D training should be organized regularly for health personnel. Pregnant classes and pregnancy school programs in wellness centers and hospitals should be used more effectively. As far as possible, healthy pediatric outpatient clinics should be opened in all hospitals.